SVM regression to assess meat characteristics of bisaro pig loins using nirs methodology - Vasconcelos, Lia (2022)
This study evaluates the ability of the near infrared reflectance spectroscopy (NIRS) to estimate the aW, protein, moisture, ash, fat, collagen, texture, pigments, and WHC in the Longissimus thoracis et lumborum (LTL) of Bisaro pig. Samples (n = 40) of the LTL muscle were minced and scanned in an FT-NIR MasterTM N500 (BuCHI) over a NIR spectral range of 4000-10,000 cm(-1) with a resolution of 4 cm(-1). The PLS and SVM regression models were developed using the spectra's math treatment, DV1, DV2, MSC, SNV, and SMT (n = 40). PLS models showed acceptable fits (estimation models with RMSE <= 0.5% and R-2 >= 0.95) except for the RT variable (RMSE of 0.891% and R-2 of 0.748). The SVM models presented better overall prediction results than those obtained by PLS, where only the variables pigments and WHC presented estimation models (respectively: RMSE of 0.069 and 0.472%; R-2 of 0.993 and 0.996; slope of 0.985 +/- 0.006 and 0.925 +/- 0.006). The results showed NIRs capacity to predict the meat quality traits of Bisaro pig breed in order to guarantee its characterization.